OP011 Integration of whole-exome sequencing and RNA sequencing of intestinal biopsies in inflammatory bowel disease identifies inflammation-dependent effects. (16th January 2018) - Barbieri, R; Uniken Venema, W; Vich Vila, A; Li, Y; Franke, L; van Dijk, F; De Klein, N; Swertz, M; Sanna, S; Voskuil, M D; Rivas, M; Xavier, R; et al.
Abstract: Background: Inflammatory bowel disease (IBD), consisting of Crohn's disease (CD) and ulcerative colitis (UC), is a chronic relapsing inflammatory disease with increasing prevalence. In recent years, 215 genetic loci have been associated with both CD and UC. The effect of genetic variation on gene expression (defined as expression quantitative expression loci—eQTLs) has been studied by combining GWAS and transcriptome data from peripheral blood. However, it is increasingly recognised that these eQTLs are tissue and context dependent. Biological processes, such as inflammation, may modulate eQTLs by altering the transcriptome regulation, which could favour the onset of disease. To study the context and tissue-dependent effects of genetic variants in IBD, we correlated whole-exome sequencing (WES) of whole blood samples to RNA-sequencing of inflamed and non-inflamed intestinal biopsies from IBD patients. Methods: We performed cis -eQTL analyses on 165 corresponding RNA-sequencing and WES samples: (i) within IBD-associated genetic regions, (ii) whole-exome wide. In addition, we assessed the effect of inflammation on eQTLs in paired inflamed and non-inflamed biopsies from 75 patients. All analyses were done using the R package Matrix-eQTL, correcting for possible confounding factors (batch, sex, age, tissue, and diagnosis). An eQTL was defined significant using an FDR threshold of 0.05. Results: We identified 96 gut mucosal eQTLs in known associated IBD loci and 1479 eQTLs exome-wide. We identified 393 inflammation-specific eQTLs; of which, 40 were identified in known IBD-associated loci. Two top inflammation-specific eQTLs are IL21 and IL17RC. IL21 is well known to play an important role in IBD, and it is known to be overexpressed in intestinal mucosa in IBD. IL21 is expressed by T and B cells, and it acts on intestinal epithelium helping to maintain Th1 inflammation and Th17 differentiation, hallmarks of IBD intestinal inflammation. IL17RC encodes the IL17RC receptor, which is structurally similar to the IL17RA receptor both of which bind IL17A and IL17F. However, while the IL17RA receptor that has a higher affinity for IL17A, which regulates inflammation, IL17RC has a higher affinity for IL17F, which exacerbates inflammation, and was recently implicated in IBD development. Anti-IL17A drugs were shown to be ineffective in the treatment of IBD, but based on these data one could consider targeting IL17F or IL17RC. Conclusions: In this study we show the following: (i) we identified 40 eQTLs that affect gene expression in the intestine during inflammation only. (ii) Perturbation of the genes involved in inflammation-dependent eQTLs is likely associated to alter disease activity in IBD. (iii) These inflammation-specific eQTLs are potential leads for drug targeting in IBD. References: 1. Sanchez-Munoz F. Role of cytokines in inflammatory bowel disease. 2008. 2. Fantini MC. New players in the cytokine orchestra of inflammatory bowel disease. 2007. 3. de Rham C. The proinflammatory cytokines IL-2, IL-15 and IL-21 modulate the repertoire of mature human natural killer cell receptors. 2007. 4. Fina D. Interleukin-21 (IL-21) controls inflammatory pathways in the gut. 2007. 5. Caruso R. A functional role for interleukin-21 in promoting the synthesis of the T-cell chemoattractant, MIP-3alpha, by gut epithelial cells. 2007. 6. Chen Z. Signal transduction pathways and transcriptional regulation in the control of Th17 differentiation. 2007. 7. Monteleone G. Interleukin-21 enhances T-helper cell type I signaling and interferon-gamma production in Crohn's disease. 2005. 8. Ho AW. IL-17RC: A partner in IL-17 signaling and beyond. 2010.